Crisis, Cruelty and Absurdism in John Ruganda’s the Floods and Shreds of Tenderness - Chepkwony, Kipkoech Mark (East African Journal of Education Studies, 2023)
John Ruganda is categorized as an African writer whose writing is marked by the expression of post-independence disillusionment and the transference of anger and blame from foreign to indigenous leaders, yet he has received very little critical attention as an artist. The study examined the aesthetics of the absurd drama in John Ruganda’s plays. The rationale for the study gestures to the need to study Ruganda’s dramatic texts as representative of a historical, cultural and social trajectory through the less studied body of drama. This study discusses the state of social and psychological crisis, cruelty and absurdism of life in drama. The study used Ruganda’s two plays, namely The Floods and Shreds of Tenderness. The various modes through which absurd drama appeals to the aesthetic sensibilities were examined. The study employed descriptive research and used purposive sampling. Data were analysed qualitatively by describing the findings of the study to arrive at inferences and conclusions. In his plays, Ruganda depicts a society full of misfortunes and suffering and where no one has peace. Each person is seen as a problem that eats up the mind and body. Many people have lost their lives because of a cruel society. The effects of cruelty are also depicted through the fragmentary nature of the characters’ lives and their minds. The state is violent to its subjects, and subjects are violent against one another